Datathons: fostering equitability in data reuse in ecology - Jurburg, Stephanie; Álvarez Blanco, María; Chatzinotas, Antonis; Kazem, Anahita; König-Ries, Birgitta; Babin, Doreen; Smalla, Kornelia; Cerecetto, Victoria; Fernandez-Gnecco, Gabriela; Covacevich, Fernanda; Leoni, Carolina; Garaycochea, Silvia; et al. (Elsevier, 2024)
Approaches to rapidly collecting global biodiversity data are increasingly important, but biodiversity blind spots persist. We organized a three-day Datathon event to improve the openness of local biodiversity data and facilitate data reuse by local researchers. The first Datathon, organized among microbial ecologists in Uruguay and Argentina assembled the largest microbiome dataset in the region to date and formed collaborative consortia for microbiome data synthesis.